The Implementation of Merdeka Curriculum in English Subject for Strengthening Pancasila Student - Umi Khasanah; Nana Priajana (STIT Buntet Pesantren Cirebon, 2024)
Curriculum changes in education intiated by the Ministry of Education and Culture emphasize the flexibility of educators and students in learning. It does not rule out the possibility that English Teaching Learning can also run effectively using a Merdeka Curriculum. The Merdeka Curriculum emphasizes the elements of Pancasila Student Profile. The aims of the research to be carried out by researchers are as follows: (1) To find the problems and solutions of teacher during the implementation of the Merdeka Curriculum For Strengthening Pancasila Student Profile in English Teaching Learning at Junior High School. (2) To know the implementation of Merdeka Curriculum For Strengthening Pancasila Student Profile in English Teaching Learning at Junior High School. This research involved six students, three teachers. The researcher used a desriptive qualitative method to do the research. Data from this research collected by Observation, Interview, and Document Analysis. The result from this research are: (1) The use of the Merdeka curriculum based on strengthening the Pancasila student profile in English learning at SMPN 2 Pangenan Cirebon runs based on three stages: planning, implementation, and evaluation. (2) There are 3 types of problems faced by English teachers in using the Merdeka curriculum for strengthening Pancasila student profile: problems based on teachers themselves, problems based on students, and problems from supporting factors. In each of these problems, there are solutions that teachers apply to overcome them.